2004
DOI: 10.1111/j.1440-1754.2004.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for infants weighing less than 1000 grams cared for with a nasal continuous positive airway pressure‐based strategy

Abstract: Improved respiratory outcomes for infants weighing less than 1000 g were evident at Middlemore Hospital. This was attributed to the use of a nasal CPAP-based respiratory support system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
(39 reference statements)
2
34
2
Order By: Relevance
“…Finally, a study from New Zealand described a lower rate of CLD (at 36 weeks' PMA) with a policy of preferential water seal bubble NCPAP delivery in ELBW infants at a single center, when compared to composite data from 28 other centers (19 vs 45%). 24 The rate of CLD in the study is considerably lower than ours, although the incidence of CLD or death is similar (40%).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Finally, a study from New Zealand described a lower rate of CLD (at 36 weeks' PMA) with a policy of preferential water seal bubble NCPAP delivery in ELBW infants at a single center, when compared to composite data from 28 other centers (19 vs 45%). 24 The rate of CLD in the study is considerably lower than ours, although the incidence of CLD or death is similar (40%).…”
Section: Discussioncontrasting
confidence: 43%
“…We also observed a trend to a decrease in late-onset infections in the Early NCPAP group, which has been described in other reports of preferential NCPAP use in the ELBW population. 21,24 This may be due to the lack of endotracheal tube as a site of colonization and a portal of entry for infection, or other differences in care that occurred as a result of the practice change but were not evaluated in our study, as duration of mechanical ventilation is only one factor associated with late-onset sepsis in preterm infants. 29 We have used historic controls in our study as a comparison group, as have other studies of preferential early NCPAP in ELBW infants published to date.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…CPAP versus intubation/mechanical ventilation is associated with decreased incidences of bronchopulmonary dysplasia and sepsis, and with a trend toward decreased rates of retinopathy of prematurity and intraventricular hemorrhage. [19][20][21] CPAP, however, may contribute to the development of benign gaseous bowel distension in neonates (CPAP belly syndrome), 22 and it may be associated with an increased rate of necrotizing enterocolitis. 19,20 It is not clear if the attenuated SMA BFV was owing to CPAP-related decreases in cardiac output, nor if bowel-related concerns with CPAP relate to our finding of attenuated increases in postnatal SMA BFV in infants on CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] CPAP, however, may contribute to the development of benign gaseous bowel distension in neonates (CPAP belly syndrome), 22 and it may be associated with an increased rate of necrotizing enterocolitis. 19,20 It is not clear if the attenuated SMA BFV was owing to CPAP-related decreases in cardiac output, nor if bowel-related concerns with CPAP relate to our finding of attenuated increases in postnatal SMA BFV in infants on CPAP. However, other investigators have reported that attenuated increases in postnatal SMA BFV are associated with intestinal dysmotility, 2 and with feeding intolerance.…”
Section: Discussionmentioning
confidence: 99%